Penguatan Self-Regulation Anak Panti Asuhan Aisyah Curup Selama Belajar Daring di Masa Pandemi Covid 19 - Beni Azwar (Institut Agama Islam Negeri Curup, 2022)
This study aims to discuss strengthening the self-regulation of orphanage children during online learning during the COVID-19 pandemic, the fact that the conditions of orphanage children are different from children living with nuclear families who always receive attention and affection, and facilitate their learning needs, while orphans do not. Get this, and the orphanage must accept this situation with no stress and sincerity. For this reason, researchers are interested in how orphanage children regulate themselves in online learning and are not stressed with the conditions at the Aisiyah Curup Orphanage. The research methodology is descriptive qualitative, where data will be collected with the interview dept (in-depth interview) and presented descriptively. The result is that strengthening self-regulation, namely metacognition, motivation and behavior, already existed during the Covid 19 pandemic, but decreased compared to before the Covid 19 pandemic. Limited facilities and family motivation were felt to be lacking, because during the pandemic the nursing home did not receive guests from outside and they behaved well with a pattern the same according to the schedule of daily routine activities arranged by the orphanage.